Implementation of Diversity Management to Increase Organizational Inclusivity in the Department of Industry, Trade, Mining and Energy in South Kalimantan Province - Riris Ambarwati; Aden Sutiapermana; Atep Jejen; Isep Amas Priatna; Nanang Rustandi; Wahyu Maulid Adha (SEAN Institute, 2024)
In the era of ever-growing globalization, diversity management has become a necessity for organizations around the world. This article explores the concept of diversity management, an approach that encourages the creation of an inclusive work environment regardless of differences such as race, gender, religion, sexual orientation, and background. Implementing diversity management has a number of benefits, including inclusiveness, creativity, positive reputation, improved performance, and legal compliance. In the context of the Department of Industry, Trade, Mining and Energy in South Kalimantan Province, diversity management becomes more important. Organizations in the province face unique diversity challenges, and diversity management is key to addressing unconscious bias, increasing team member participation, and creating conditions that support diversity. However, diversity challenges in organizations include discrimination, unequal access, resistance to change, ineffective communication, difficulty creating an inclusive culture, and meeting diverse customer expectations. This study uses quantitative research methods to identify the relationship between effective diversity management and organizational inclusivity. In conclusion, diversity management is the key to creating inclusive, innovative and high-performing organizations. Concrete recommendations can help organizations such as the Department of Industry, Trade, Mines and Energy in South Kalimantan Province in implementing concrete steps to increase inclusiveness. This article offers a comprehensive view of diversity management and illustrates the importance of this approach in addressing diversity challenges in global and local contexts.